2019
DOI: 10.3390/polym11061020
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Evaluation, on Polyurethane Foam Sheets, of the Insertion Torque (IT) Values, Pull-Out Torque Values, and Resonance Frequency Analysis (RFA) of NanoShort Dental Implants

Abstract: Objectives: The aim of this study was to investigate, in polyurethane foam sheets, the primary implant stability of a NanoShort implant compared to a self-condenser implant and to a standard, conventional implant. Materials and Methods: Three implant designs were evaluated in the present in vitro investigation: The Test implant (NanoShort), the Control A implant (self-condenser), and the Control B implant (standard design). The study was conducted by comparing the insertion torque values, the pull-out strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
1
37
0
2
Order By: Relevance
“…The main reason for measuring the implant primary stability concerns the ability to predict the prognosis of the dental implant procedure. Comuzzi et al, in vitro, reported that in polyurethane foam, ISQ, insertion torque, and pull-out measuring provide the high repeatability and reproducibility that represent suitable indicators for implant stability [26]. In the present investigation, the implant primary stability was evaluated in a controlled reproducible study design and without the variables correlated to the use of animal bone.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The main reason for measuring the implant primary stability concerns the ability to predict the prognosis of the dental implant procedure. Comuzzi et al, in vitro, reported that in polyurethane foam, ISQ, insertion torque, and pull-out measuring provide the high repeatability and reproducibility that represent suitable indicators for implant stability [26]. In the present investigation, the implant primary stability was evaluated in a controlled reproducible study design and without the variables correlated to the use of animal bone.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, implants with a conical shape have a high stability even in blocks with a low density (D4 Density) and no differences were found between 5 mm and 6 mm long implants, where reasonable values of insertion torque and pull-out tests were found in short implants in both polyurethane densities. Comuzzi et al reported in vitro that a conical shape, rather than a cylindrical design, provided increased values of insertion torque and pull-out strength [26]. Thus, the ISQ values of both short implants were great, with an increased clinical sensation of the high stability of the implants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we used a polyurethane foam density of 0.48 g/cm 3 in the cortical portion, considering that the mean of cortical bone density in human maxilla is 0.31 g/cm 3 for the posterior area and 0.45 g/cm 3 for the anterior area [29]. The densities of polyurethane foam used in the present study was of 15 pounds per cubic foot (pcf), corresponding to a density of 0.24 g/cm 3 (similar to the D3 bone type by Mish [30,31]); and 40 pcf, corresponding to 0.55 g/cm 3 (similar to D1 bone by Mish [30,31]). Cancellous bone receives and dissipates the forces generated by mastication after implant osseointegration more efficiently; however, to obtain the initial stability, cortical bone is more important because it has high density and resistance (~40% more) in comparison to medullary bone [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, this method revealed the absence of mobility of the installed implant and not the bone quantity at the implant-bone interface [35,36]. The determination of good osseointegration is directly related to the absence of movement at the bone-implant interface in the different types of bone density [31]. Therefore, the lack of micromovement determined by a rigid primary stability and healing period free from external stimuli is originally a prerequisite for obtaining a satisfactory clinical result [37].…”
Section: Discussionmentioning
confidence: 99%
“…The resonance frequency analysis (RFA) is a repeatable technique for implant stability evaluation that provides a measurement of the micromovements of the implant positioned in the bone site [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%